Harry Potter and the deathly hallows - Rowling, J. K. (Scholastic Inc., 2018)
With the future of the wizard world at stake, teenaged wizard Harry Potter enters into his final battle against the evil Lord Voldemort. Potter turns to friends, teachers, and other members of the Order of the Phoenix for help in defeating Voldemort's forces. The discovery of spies within the Order forces Harry and the others to choose their allies carefully.